Influence of a cubic wood particle orientation in space on the characteristics and conditions of its ignition. (March 2023) - Kuznetsov, G.V.; Syrodoy, S.V.; Kostoreva, Zh.A.; Kostoreva, A.A.; Malyishev, D. Yu.; Nigay, N.A.; Gutareva, N. Yu.
Abstract: The article presents the results of the experimental and theoretical studies of the ignition processes of dry particles of woody biomass with a wide variation in heating conditions. A detailed analysis of the typical frames of the videogram has shown that the temperature of the oxidizing agent affects the nature of the ignition process of a wood particle. Under conditions of moderate ambient temperatures (Tg ≤ 873K), ignition, as a rule, occurs in the gas region under the particle. At the same time, the ignition of wood particles under conditions of high-temperature heating (at Tg > 1073K) proceeds in the gas phase in a small (very thin) neighborhood around the wood particle along its entire perimeter. A model is formulated that describes the ignition under the considered rather typical conditions and differs from the known description of the processes of convection of gaseous pyrolysis products during the induction period. Based on the results of the experiments, the influence of the type of woody biomass on the characteristics and conditions of ignition of fuel particles has been analyzed. It has been established that dry particles of woody biomass made of pine under relatively low ambient temperatures (at T g ≤873 K ) ignite much faster compared to particles of similar size from birch, aspen and cedar. Differences in ignition delay times reach 90%. At high ambient temperatures ( T g ≥1273K ), the ignition delay times of all four investigated fairly typical types of woody biomass differ insignificantly (the deviation of the ignition delay times does not exceed 5%). The analysis of the influence of the orientation of wood fibers in space relative to the direction of the heat flow vector on the characteristics and conditions of ignition has also been carried out. It is shown that the orientation of the wood particle in space does not significantly affect the characteristics and conditions of ignition. This trend has been registered for all four types of wood studied. Highlights: The ignition mechanism of a wood particle depends on the temperature of the oxidizer. Pine particles ignite faster than birch, cedar and aspen particles at low temperatures. The type of wood does not affect the ignition dynamics at high ambient temperatures. The anisotropy of thermophysical properties does not affect the ignition dynamics.